1998
DOI: 10.1074/jbc.273.18.11127
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Split Respiratory Pathway in the Wheat “Take-all” Fungus, Gaeumannomyces graminis var.tritici

Abstract: This article describes the first detailed analysis of mitochondrial electron transfer and oxidative phosphorylation in the pathogenic filamentous fungus, Gaeumannomyces graminis var. tritici. While oxygen consumption was cyanide insensitive, inhibition occurred following treatment with complex III inhibitors and the alternative oxidase inhibitor, salicylhydroxamic acid (SHAM). Similarly, maintenance of a ⌬ across the mitochondrial inner membrane was unaffected by cyanide but sensitive to antimycin A and SHAM w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 20 publications
2
33
0
1
Order By: Relevance
“…But interestingly, M. nivale strains were highly sensitive to nPG on PDA. Similar high sensitivity to AOX inhibitors has been reported for Gaeumannomyces graminis and Tapesia acuformis (Joseph-Horne et al 1998. These results suggested that both complex III and AOX are necessary for fundamental respiration even under typical growth conditions.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…But interestingly, M. nivale strains were highly sensitive to nPG on PDA. Similar high sensitivity to AOX inhibitors has been reported for Gaeumannomyces graminis and Tapesia acuformis (Joseph-Horne et al 1998. These results suggested that both complex III and AOX are necessary for fundamental respiration even under typical growth conditions.…”
Section: Discussionsupporting
confidence: 76%
“…Bars represent the standard deviation of the mean. Different letters above columns indicate significant difference at the 5% level according to Duncan's multiple range test the ATP level in G. graminis (Joseph-Horne et al 1998). Additionally, AOX protein was constitutively present in several fungi such as G. graminis, B. cinerea, Histoplasma capsulatum and Blastomyces dermatitidis (Joseph-Horne et al 1998;Johnson et al 2003;Tamura et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, the mitochondrial membrane potential remains unchanged, as is expected because of the non-proton-pumping nature of the AOX (48). In contrast, in filamentous fungi and yeasts respiring simultaneously by complex IV and AOX, a rapid collapse of the mitochondrial membrane potential is observed (46,47,49,50). Interestingly, the AOX-dependent respiratory chain in the filamentous fungus P. anserina, in which the AOX is only induced by the specific deficiency of complex IV (51), as in some other fungi (e.g.…”
Section: Is the Plant Respiratory Chain Organized In A More Dynamic Mmentioning
confidence: 73%
“…In the rest of fungi the AOX expression and activity are very complex and highly diverse among different species. In some like Aspergillus niger (Kirimura et al 1987), Gaeumannomyces graminis (Joseph-Horne et al 1998) and Candida parapsilosis (Milani et al 2001) AOX is both constitutively present and active component of the electron transport chain, in others like Allomyces macrogynus (Heldt-Hansen et al 1983a) and Ustilago maydis (Juárez et al 2006) it becomes active only after inhibition of CSR, while in fungi like Neurospora crassa, (Tanton et al 2003) and Magnaporthe grisea, (Yukioka et al 1998) inhibition of CSR, or some other environmental stimuli, is necessary for induction of AOX expression.…”
Section: Introductionmentioning
confidence: 97%